The role of bilingualism in executive functions in healthy older adults: a systematic review - Degirmenci, Merve Gul; Großmann, Judith; Meyer, Patric; Teichmann, Birgit (International journal of bilingualism, 2022)
Aims and Objectives:Bilinguals have been claimed to develop superior executive functioning compared to monolinguals due to their continuous experience of controlling two languages. Given the developmental trajectory of executive functions, a bilingual advantage could be more pronounced at an advanced age. To gain a clearer understanding, we reviewed the effect of bilingualism executive functions in healthy older adults.Methodology:The present paper systematically examines the methods and the results of 24 studies from 22 articles comparing healthy older monolinguals and bilinguals in at least one domain of executive functions.Data and Analysis:Data of each study were extracted for sample characteristics, country, language background and measures, controlled confounders and task paradigms. Study quality was also calculated for each study.Findings and Conclusions:In general, nine out of the 24 studies fully supported the notion of a bilingual advantage. Four studies showed a bilingual disadvantage. The rest of the studies challenged the existence of a bilingual advantage, as neither full support for bilingual advantages nor bilingual disadvantages were seen in various domains. The available data did not clearly support the widespread notion that bilingualism is related to a general advantage in executive control. However, when looking at the domains of executive functions separately, bilingualism was reliably associated with an advantage in inhibition, especially in two commonly applied tasks: the Stroop test and the Simon task.Originality:This is the first systematic review aimed at exploring the link between bilingualism and executive functions in healthy older adults.Significance/Implications:Heterogeneity in study characteristics and control of confounding variables may partially explain some of the inconsistencies found between studies. Therefore, well-designed studies that measure all core domains of executive functions and consider confounding variables are urgently needed.